Medicalization and its Discontents: Gender, the History of Medicine, and Nora Jaffary’s Reproduction and Its Discontents - Ramos, Christina (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2018)
This essay discusses Jaffary’s award-winning book in light of its contribution to the history of medicine. Reproducton and Its Discontents makes crucial scholarly inroads in two fundamental ways: first, by building on feminist scholarship that has examined the rise of male expertise on matters of reproduction and gynecology, while simultaneously rejecting narratives of a “golden age” in women’s healthcare; second, by inserting discussions of medicine and gender into Latin America’s burgeoning medical history. At its heart, Jaffary’s book meticulously deals with the medicalization of the female body, its national and local manifestations, and its striking limitations and costs.